Anesthesia Student Survival Guide A Case-Based Approach - Ehrenfeld, Jesse M.; Urman, Richard D.; Segal, Scott; SpringerLink (Online service) (2010)
Anesthesia Student Survival Guide: A Case-Based Approach is an indispensable introduction to the specialty. This concise, easy-to-read, affordable handbook is ideal for medical students, nursing students, and others during the anesthesia rotation. Written in a structured prose format and supplemented with many diagrams, tables, and algorithms, this pocket-sized guide contains essential material covered on the USMLE II-III and other licensing exams. The editors, who are academic faculty at Harvard Medical School, summarize the essential content with 32 informative and compelling case studies designed to help students apply new concepts to real situations. Pharmacology, basic skills, common procedures and anesthesia subspecialties are covered, too, with just the right amount of detail for an introductory text. The unique book also offers a section containing career advice and insider tips on how to receive good evaluations from supervising physicians. With its combination of astute clinical instruction, basic science explanation, and practical tips from physicians that have been there before, this handbook is your one-stop guide to a successful anesthesia rotation.
Preoperative Considerations -- The Preoperative Patient Evaluation -- Airway Evaluation and Management -- The Anesthesia Machine -- Anesthesia Equipment and Monitors -- Intraoperative Considerations -- Anesthetic Techniques: General, Sedation, MAC -- Anesthetic Techniques: Regional -- Electrolytes, Fluids, Acid-Base Analysis, and Transfusion Therapy -- IV, Gastric Tube, Arterial & Central Line Placement Techniques -- Common Intraoperative Problems -- Systems Physiology and Anesthetic Subspecialties -- Physiology and Anesthesia for Cardiac and Thoracic Surgery -- Physiology and Anesthesia for Neurologic, ENT, and Ophthalmologic Surgery -- Physiology and Anesthesia for Obstetrics -- Physiology and Anesthesia for General and Bariatric Surgery -- Anesthesia for Urological Surgery -- Physiology and Anesthesia for Pediatric Surgery -- Physiology and Anesthesia for Elderly Patients -- Ambulatory Surgery and Out-of-OR (OOR) Procedures -- Anesthesia for Trauma and Orthopedic Surgery -- Postoperative Considerations -- Perioperative Acute and Chronic Pain Management -- Postoperative Anesthesia Care Unit (PACU) and Common Postoperative Problems -- to Critical Care -- Special Topics -- Professionalism, Safety, and Teamwork -- Quality Assurance, Patient and Provider Safety -- Ethical and Legal Issues in Anesthesia -- Clinical Simulation in Anesthesia Education -- to Anesthesiology -- How to Be a (3z(BStar(3y (BStudent, Career Options, and the Match -- History of Anesthesia and Introduction to the Specialty -- Pharmacology -- Pharmacology Principles -- Pharmacology of Intravenous Anesthetic Agents -- Pharmacology of Inhalational Anesthetics -- Pharmacology of Local Anesthetics -- Pharmacology of Adjunct Agents.s
Keywords: Medicine; Anesthesiology; Medicine & Public Health; Anesthesiology